IMPACT OF CORPORATE GOVERNANCE FAILURE ON PUBLIC TRUST: AN EVIDENCE FROM INDIA - Kukreja, Gagan (International Journal of Accounting & Finance Review, 2021)
This research study explores the maligned role of Chanda Kochhar, the top-notch executive of ICICI Bank, a leading multinational and financial service provider. An alleged corruption case was filed against her under the Prevention of Money Laundering Act. The case was filed against her after a whistleblower alleged that the bank had given INR 32.50 billion to Videocon group in 2012, the majority of which was declared as Non- Performing Assets later by the bank. This research study focuses on misused the position for personal gains. It touches upon the board of directors of an organisation’s fiduciary role and tries to outline whistleblowers’ importance in corporate governance. The study unravels the conflicts of interest, alleged corruption, lack of disclosures of related party transactions required by corporate governance principles, and quid-pro-quo. The study will deliberate the impact of such alleged corruption on the various stakeholders, especially shareholders. The study is exploratory and qualitative and based on publicly available information. Other corroborative evidence verifies the reliability of the information. This study will offer suggestions to improve the corporate governance principles to the regulators. JEL Classification Codes: D73, D74, G21, G34.